2019
DOI: 10.1186/s12876-019-1126-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the controlling nutritional status (CONUT) score in patients undergoing hepatectomy for hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: BackgroundThe clinical value of the controlling nutritional status (CONUT) score in hepatocellular carcinoma (HCC) has increased. The aim of this meta-analysis was to systematically review the association between the CONUT score and outcomes in patients undergoing hepatectomy for HCC.MethodsEmbase, Medline Ovid, Web of Science, Cochrane CENTRAL, and Google Scholar were systematically searched. Random effects meta-analyses were conducted to examine the prognostic value of the CONUT score in HCC patients.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…Previous studies have reported that ALBI grade, AFP level, and BCLC stage are independent factors for OS in patients with HCC treated with LEN [7,9], indicating that our results showed good agreement with those of previous reports. The CONUT score has previously been reported as a prognostic factor for patients with HCC treated with hepatic resection [24,25,34]. However, we are the first to reveal that the CONUT score is an independent factor for OS in patients with HCC treated with LEN.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Previous studies have reported that ALBI grade, AFP level, and BCLC stage are independent factors for OS in patients with HCC treated with LEN [7,9], indicating that our results showed good agreement with those of previous reports. The CONUT score has previously been reported as a prognostic factor for patients with HCC treated with hepatic resection [24,25,34]. However, we are the first to reveal that the CONUT score is an independent factor for OS in patients with HCC treated with LEN.…”
Section: Discussionmentioning
confidence: 50%
“…The CONUT score has been reported to predict the risk of postoperative complications of grades III-V [23], as well as the prognosis of patients who undergo hepatic resection for HCC [24,25]. Thus, the CONUT score is a useful index for the management of patients who undergo hepatic resection for HCC; however, the impact of a CONUT score on the prognosis for HCC patients treated with LEN has been unclear until now.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported the association between the CONUT score and complications in multivariable analyses [10,18], in contrast no association between the CONUT score and postoperative infectious diseases was shown [14,15]. Recent meta-analyses have indicated that patients with higher CONUT score had an increased risk of complications as well as mortality after gastroenterological and hepatopancreatobiliary surgery [6][7][8]. Therefore, the CONUT score might be helpful in predicting complication risks in CRC surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The queries were constructed using suitable terms concerning the CONUT score and CRC (Supplementary Table 1). The methods of our systematic literature review strategy have been described previously [6][7][8]. No ethical approval or informed consent statement was required for this review article.…”
Section: A Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation